Contemporary Black biography. profiles from the international Black community. (Gale virtual reference library, 2009)
Biographical profiles of important and influential persons of African heritage who form the international black community. Covers persons of various nationalities in a wide variety of fields providing coverage of names found in today's headlines as well as selected individuals from earlier in this century whose influence continues to have an impact on contemporary life.